Defining catastrophic costs and comparing their importance for adverse tuberculosis outcome with multi-drug resistance: a prospective cohort study, Peru. - Tom Wingfield; Delia Boccia; Marco Tovar; Arquímedes Gavino; Karine Zevallos; Rosario Montoya; Knut Lönnroth; Carlton A Evans (PLoS Medicine)
Background Even when tuberculosis (TB) treatment is free, hidden costs incurred by patients and their households (TB-affected households) may worsen poverty and health. Extreme TB-associated costs have been termed "catastrophic" but are poorly defined. We studied TB-affected households' hidden costs and their association with adverse TB outcome to create a clinically relevant definition of catastrophic costs. Methods and findings From 26 October 2002 to 30 November 2009, TB patients (n = 876, 11% with multi-drug-resistant [MDR] TB) and healthy controls (n = 487) were recruited to a prospective cohort study in shantytowns in Lima, Peru. Patients were interviewed prior to and every 2-4 wk throughout treatment, recording direct (household expenses) and indirect (lost income) TB-related costs. Costs were expressed as a proportion of the household's annual income. In poorer households, costs were lower but constituted a higher proportion of the household's annual income: 27% (95% CI = 20%-43%) in the least-poor houses versus 48% (95% CI = 36%-50%) in the poorest. Adverse TB outcome was defined as death, treatment abandonment or treatment failure during therapy, or recurrence within 2 y. 23% (166/725) of patients with a defined treatment outcome had an adverse outcome. Total costs ≥20% of household annual income was defined as catastrophic because this threshold was most strongly associated with adverse TB outcome. Catastrophic costs were incurred by 345 households (39%). Having MDR TB was associated with a higher likelihood of incurring catastrophic costs (54% [95% CI = 43%-61%] versus 38% [95% CI = 34%-41%], p<0.003). Adverse outcome was independently associated with MDR TB (odds ratio [OR] = 8.4 [95% CI = 4.7-15], p<0.001), previous TB (OR = 2.1 [95% CI = 1.3-3.5], p = 0.005), days too unwell to work pre-treatment (OR = 1.01 [95% CI = 1.00-1.01], p = 0.02), and catastrophic costs (OR = 1.7 [95% CI = 1.1-2.6], p = 0.01). The adjusted population attributable fraction of adverse outcomes explained by catastrophic costs was 18% (95% CI = 6.9%-28%), similar to that of MDR TB (20% [95% CI = 14%-25%]). Sensitivity analyses demonstrated that existing catastrophic costs thresholds (≥10% or ≥15% of household annual income) were not associated with adverse outcome in our setting. Study limitations included not measuring certain "dis-saving" variables (including selling household items) and gathering only 6 mo of costs-specific follow-up data for MDR TB patients. Conclusions Despite free TB care, having TB disease was expensive for impoverished TB patients in Peru. Incurring higher relative costs was associated with adverse TB outcome. The population attributable fraction indicated that catastrophic costs and MDR TB were associated with similar proportions of adverse outcomes. Thus TB is a socioeconomic as well as infectious problem, and TB control interventions should address both the economic and clinical aspects of this disease. Please see later in the article for the Editors' Summary.